2015
DOI: 10.1016/j.nutres.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status is inversely associated with obesity in a clinic-based sample in Puerto Rico

Abstract: Studies show that vitamin D status is associated to obesity but data in Hispanic individuals is scarce. The aim of this study was to assess the association between vitamin D status and obesity in a clinic-based sample in Puerto Rico. We hypothesized that subjects with a higher adiposity would have a lower vitamin D status. We extracted the following data from medical records of a private clinic: age, gender, serum 25(OH)D levels, weight, height, and waist circumference. BMI (kg/m2) and waist-to-height ratio we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 40 publications
4
30
0
2
Order By: Relevance
“…Our study found a positive association between low vitamin D status (25(OH)D ≤ 30 ng/mL) and PBF, which is also concordant with the literature [17,25,34,44]. While this relationship is not fully understood, it is assumed that since vitamin D is a fat soluble vitamin, it might be sequestered in the excess adipose tissue of obese adults and would be slowly released at negative energy balance [17]. Further, a potential confounder is that obesity is also linked to an unhealthy lifestyle, characterized by less physical activity, less sun exposure and, hence, lower vitamin D concentrations [45].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study found a positive association between low vitamin D status (25(OH)D ≤ 30 ng/mL) and PBF, which is also concordant with the literature [17,25,34,44]. While this relationship is not fully understood, it is assumed that since vitamin D is a fat soluble vitamin, it might be sequestered in the excess adipose tissue of obese adults and would be slowly released at negative energy balance [17]. Further, a potential confounder is that obesity is also linked to an unhealthy lifestyle, characterized by less physical activity, less sun exposure and, hence, lower vitamin D concentrations [45].…”
Section: Discussionsupporting
confidence: 93%
“…The association of adiposity, measured by WC and PBF, with serum 25(OH)D is usually stronger than that with BMI [43]. In concordance with our results, multiple studies showed that vitamin D concentrations were significantly lower in both males and females with high risk WC compared to low risk categories (p < 0.05) [9,11,17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Yet, intermediate biomarker of obesity demonstrated an inverse relationship between adiposity and low vitamin D levels. 32 However, as highlighted by Ibero-Baraibar et al, 33 no causal relationship has been proved. Note also that, this relationship could be also altered by the volumetric dilution and sequestration of vitamin D in adipose tissue.…”
Section: Potential Role Of Vitamin D In Obesitymentioning
confidence: 98%
“…Body mass index is negatively associated with vitamin D status [31,32,33,34,35] and vitamin D inadequacy is highly prevalent among children who are overweight or obese compared to non-overweight children [1]. Obese children may have elevated vitamin D requirements due to the sequestration of lipid-soluble vitamin D in a larger pool of adipose tissues [6,35,36], lower vitamin D metabolism in the liver [36], increased vitamin D catabolism in the kidneys [6,36], or limited sun exposure due to low physical activity levels [36].…”
Section: Discussionmentioning
confidence: 99%